Society-Based Water Management in Passo Village in Baguala Sub-District, City of Ambon - Herwic Krisjuardto Pinoa; Bagyo Yanuwiadi; Wike Wike (The Indonesian Green Technology Journal, 2019)
The objective of this study is to find out the availability of water, the distribution of spring locations, the amount of clean water needs, and the right strategy to maximize the management of clean water in Passo Village. To obtain the right management strategy, the SWOT method was applied in this study. Based on the results of SWOT analysis, it was found that the proposed alternative management strategy related to stable growth is directed at strengthening collaborative and participatory management by relying on the strength of costs or funds owned by the government and opportunity from society in management implementation. The three strategies consist of developing individual or family water management sites into society-based ones, improving water quality by maintaining vegetation around the springs, and developing sites for optimal water management by creating cooperation between society and the government in order to continue to meet the needs of society. The three strategies are expected to maximize society-based clean water management in Passo Village in Baguala Sub-District, City of Ambon.Keywords: Strategy, Water Management, SWOT